Penerapan Model Discovery Learning untuk Meningkatkan Hasil Belajar Siswa Pada Tema Peduli Makhluk Hidup Siswa Kelas IV SD Inpres Mamajang II Kota Makassar - Sri Hastati (STKIP Andi Matappa Pangkep, 2022)
The low learning outcomes of fourth graders at SD Inpres Mamajang II Kota Makassar. For this reason, it is necessary to apply the Discovery learning model to improve student learning outcomes. The research used is the Kemmis and Taggart class action research (CAR), with 9 research subjects in grade IV at SDI Mamajang II. This study consisted of 2 cycles, each cycle consisting of stages of planning, implementation, observation, and reflection. Data collection techniques used in this study were observation, interviews and multiple choice tests. The results showed that there was an increase in the average score of students in the first cycle which was 66.67 and in the first cycle it increased to 81.11. Mastery of student learning in the first cycle is 44,44% and in the second cycle has increased to 88.89%. The application of the Discovery learning model can improve the learning outcomes of fourth grade students at SD Inpres Mamajang II Kota Makassar.